Ruweda - Espia, Hannah Tabitha Madrazo (2012)
"In the Philippines, a country that relies on gambling, game shows and the lottery as a quick-fix for poverty, the concept of luck or "swerte" plays a big role in the lives of the people. Ruweda is film about the cost of a person's luck. The concept is based on the adage that "there is no such thing as a free lunch," which means that anything that is freely given to an individual is actually paid for by someone else. Guided by the Theory of Probability and the narrative structure of Hyperlink Cinema Ruweda tells a story of luck, risk and hope."